Experimental study on combustion and unregulated emission characteristics of a diesel engine fueled with light hydrocarbon/diesel blends. (1st May 2022) - Chen, Hanyu; Cheng, Yong; He, Qigeng; Wang, Xi
Highlights: Blended fuel by blending diesel and LHC were tested in CI engine. Combustion and unregulated emissions can be improved by LHC/diesel engine. Semi-quantitative method with the peak area was utilized to represent the relative concentrations of substances. Impact of different load conditions on unregulated emission is analyzed. Abstract: Rigorous emission regulations are provoking to pursue substitute of diesel with clean and sustainable alternative fuels to work out the problem of the regulated and unregulated emissions and diesel depletion. In this paper, the partial load characteristics of emission especially unregulated and combustion characteristics of a six-cylinder compression ignition diesel engine fueled with conventional diesel and 85% light hydrocarbon (LHC)-diesel blends were investigated and compared at the load points of 50%, 75% and 100% and the speed of 1000 rpm. Gas chromatography-mass spectrometry (GC–MS) technology was utilized to identify components of both tested fuel and unregulated emissions. The cylinder pressure, pressure rise rate, indicated power, heat release rate and emissions were comparatively analyzed between these two fuels. The gaseous pollutants including NOx, CO and total hydrocarbon (THC) are determined by gas analyzer. Based on the experimental results, blending LHC extend the ignition delay period, thus leading to its combustion phase lag behind that of diesel fuel by 3°CA. Significant reduction in specific NOx and CO emissions was noted while THC emission is higher in engine fueling LHC/diesel blends. The dominant unregulated pollutants primarily include organosilicon compounds (OSC), aromatic compounds (AC), and non-aromatic hydrocarbons and their derivatives (NAHC). The determinant factors on OSC emissions are summarized into the content of antifoaming agents in lubricants and the load conditions. The AC emissions of both fuels have an ascending tendency with the increase of load and the AC emissions of LHC/diesel blends are obviously less than that of pure diesel. The NAHC emissions usually appear under higher load conditions with regard to LHC blends and the content is far lower than that of diesel. In a word, blending diesel with LHC significantly contributes to improve both combustion and emission characteristics.